E-learning: development of a model to assess the acceptance and readiness of technology among language learners. Issue 5 (26th July 2021) - Rafiee, Marzieh; Abbasian-Naghneh, Salman
Abstract: In recent decades, the rapid advances in technology have led many researchers to investigate the factors influencing its successful implementation in different fields. The current study, hence, aimed to identify the factors affecting e-learning acceptance and readiness in the context of foreign language learning. By reviewing the related literature, a number of hypotheses were formed and a framework was developed. A number of university students majoring in English teaching were asked to fill out the study's quantitative survey. The collected data were analyzed using smart partial least squares (smartPLS) software. The results indicated the complex relationships between the perceived usefulness, perceived ease of use, e-learning motivation, online communication self-efficacy and language learners' acceptance and readiness of e-learning. Furthermore, the findings revealed that perceived enjoyment did not have influence on e-learning acceptance and readiness among language learners through the mediating role of perceived usefulness.